Development of the Meaning in Life Measure. Issue 2 (3rd April 2019) - Hill, Clara E.; Kline, Kathryn V.; Miller, Matthew; Marks, Ellen; Pinto-Coelho, Kristen; Zetzer, Heidi
Abstract: To correct problems identified in existing measures of meaning in life (MIL) (lack of inclusion of items related to felt sense, mattering, and reflectivity), a new 8-item Meaning in Life Measure (MILM) was developed. Two subscales emerged: Experience (MILM-E, with items related to felt sense, mattering, goals, coherence) and Reflectivity (MILM-R, with items related to valuing thinking about meaning). High internal consistency and test–retest reliability were found for both subscales. Concurrent validity was demonstrated by a strong positive correlation between MILM-E and the Meaning in Life Questionnaire-Presence (MLQ-P), and a moderate correlation between MILM-R and the Meaning in Life Questionnaire-Search (MLQ-S). For both subscales, small to moderate positive correlations were found with subjective well-being, extraversion, conscientiousness, openness, agreeableness, self-deception, and impression management; moderate negative correlations were found with depression and emotional instability. Participants who were older, female, of higher income, and married with children scored slightly higher than their counterparts on MILM-E; women scored slightly higher than men on MILM-R. We concluded that the MILM has good psychometric properties and that MIL seems to be composed of two factors.